Short- and Long-Term Antidepressant Clinical Trials for Major Depressive Disorder in Youth: Findings and Concerns - Safer, Daniel J.; Zito, Julie Magno (Frontiers in Psychiatry, 2019)
Short and Long-term Antidepressant Clinical Trials for Major Depressive Disorder in Youth: Findings and Concerns Abstract The diagnosis of major depressive disorder (MDD) in U.S. youth is increasing as is the rate of antidepressant medication (ADM) treatment for the disorder. Fluoxetine and escitalopram are FDA approved for the short term and maintenance treatment of MDD in youth. Placebo-controlled short-term ADM trials represent the basis for FDA approval. Placebo substitution / drug discontinuation trials of ADM responders represent the basis for FDA approval of ADM maintenance treatment. Meta-anlyses in 2007 and 2016 reveal that short term ADM treatment of youth diagnosed with MDD results in no meaningful controlled trial benefit for children and only marginal benefit for adolescents. ADM placebo- substitution /drug discontinuation maintenance trials are characterized by high dropout rates, a rapid withdrawal that often follows the switch to placebo, and relapse rates that are not dissimilar to those in youth experiencing the natural course of the disorder. Without the evidence from problematic ADM placebo substitution trials, there is no acceptable support for the inclusion of ADM in maintenance treatment for MDD in youth.